PENGARUH LINGKUNGAN KERJA FISIK DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI PADA KEMENTERIAN BPSDM HUKUM DAN HAM KOTA DEPOK - Shela Marlina; Irfan Rizka Akbar (Journal of Research and Publication Innovation, 2025)
This study aims to test and analyze the influence of physical work environment and work discipline on employee performance at the Ministry of Human Resources Development, Law and Human Rights, Depok City. The data collection method in this study was carried out by distributing questionnaires to a population of 80 employees. The research method used is the quantitative method of primary and secondary data. Data analysis techniques used are validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, correlation coefficient, simple linear regression, multiple linear regression, determination coefficient, and hypothesis test. Hypothesis testing partially physical work environment variable (X1) obtained t count value> t table (2.307> 1.99125) This is reinforced by a significance value of 0.000 <0.05. This means that the physical work environment has a significant effect on employee performance. Statistical test of work discipline variable (X2) obtained t count value> t table (5.496> 1.99125) this is also reinforced by a significance value of 0.000 <0.05. This means that work discipline has a significant effect on employee performance. Simultaneous hypothesis testing obtained a calculated f value > f table or (52.587 > 3.12) this is also strengthened by a significant probability value of 0.000 < 0.05. So it can be said that the physical work environment and work discipline have a significant effect simultaneously on employee performance. The coefficient of determination obtained an R Square value of 0.577, meaning that the variables of the physical work environment and work discipline together have a contribution of 57.7 to employee performance. While the remaining 42.3% is influenced by other factors not examined in this study.